Anterior Cruciate Ligament Length in Pediatric Populations: An MRI Study. Issue 4 (23rd April 2021) - Tran, Emily P.; Dingel, Aleksei B.; Terhune, E. Bailey; Segovia, Nicole A.; Vuong, Brian; Ganley, Theodore J.; Fabricant, Peter D.; Green, Daniel W.; Stavinoha, Tyler J.; Shea, Kevin G.
Background: As regards anterior cruciate ligament (ACL) reconstruction (ACLR), graft diameter has been identified as a major predictor of failure in skeletally mature patients; however, this topic has not been well-studied in the higher risk pediatric population. Hamstring tendon autograft configuration can be adjusted to increase graft diameter, but tendon length must be adequate for ACLR. Historical parameters of expected tendon length have been variable, and no study has quantified pediatric ACL morphology with other osseous parameters. Purpose: To develop magnetic resonance imaging (MRI)–derived predictors of native ACL graft length in pediatric patients so as to enhance preoperative planning for graft preparation in this skeletally immature patient population. Study Design: Cross-sectional study; Level of evidence, 3. Methods: MRI scans of 110 patients were included (64 girls, 46 boys; median age, 10 years; range, 1-13 years). Patients with musculoskeletal diseases or prior knee injuries were excluded. The following measurements were taken on MRI: ACL length; sagittal and coronal ACL inclination; intercondylar notch width and inclination; and femoral condyle depth and width. Associations between these measurements and patient sex and age were investigated. Univariate linear regression and multivariable regression models were created for each radiographic ACL measure to compare R 2 . Results: Female ACL length was most strongly associated with the depth of the lateral femoral condyle as viewed in the sagittal plane ( R 2 = 0.65; P < .001). Other statistically significant covariates of interest included distal femoral condylar width, age, and coronal notch width ( P < .05). For males, the ACL length was most strongly associated with the distal femoral condyle width as viewed in the coronal plane ( R 2 = 0.70; P < .001). Other statistically significant covariates of interest for male ACL lengths were lateral femoral condyle depth, age, and coronal notch width ( P < .05). Conclusion: In pediatric populations, femoral condylar depth/width and patient age may be valuable in assessing ACL size and determining appropriate graft dimensions and configuration for ACLRs. The use of this information to optimize graft diameter may lower the rates of ACL graft failure in this high-risk group.